A superhydrophobic/superoleophilic rGO modified melamine sponge for efficient oil sorption under static, continous and photothermal condition. (10th June 2023) - Qi, Xinyu; Gao, Zhuwei; Li, Chengxin; Wang, Shihao; Zou, Xin; He, Lan; Cui, Hao; Liu, Zhongxin
Abstract: Sponges have been widely studied as common adsorbent materials. There is little research on sponges that can be used for comprehensive treatment of oil-water mixtures, emulsions and high viscosity oils. We prepared a graphene melamine sponge (rGOMS) adsorbent material with special wettability for oil water separation by loading rGO on melamine sponge. The results showed that the water contact angle of the rGOMS prepared with GO concentration of 4.5 mol/mL (4.5-rGOMS) was 153.3° and the oil contact angle in air was 0°, indicating that 4.5-rGOMS has superhydrophobicity and superlipophilicity. The 4.5-rGOMS possessed a high saturation sorption capacity, which had values between 54.6 g/g and 132.9 g/g, and did not decrease significantly after several cycles. 4.5-rGOMS had a fast separation capacity for carbon tetrachloride/water mixtures and water-in-oil emulsions, and could achieve efficient continuous separation of n-hexane-water mixtures by connecting a peristaltic pump. Graphical abstract: Image 1 Highlights: Excellent hydrophobic performance with a water contact angle of 153.3° in air. The loss rate of adsorption capacity of oil is less than 16.6% after 10 cycles. The sponge can continuously absorb 10 mL of oil through peristaltic pump within 15s. Photothermal temperature can rise to 74.9 °C in 180s and absorb thick oil quickly.